THE EFFECT OF COOPERATIVE MODEL TYPE OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) ASSISTED WITH VIDEO MEDIA LEARNING ON THE INTERACTION OF LIVING THINGS WITH THEIR ENVIRONMENT ON STUDENT LEARNING OUTCOMES - Diah Permatasari; Elok Sudibyo; Mohammad Budiyanto (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2022)
The goal of this study is to determine how the Student Team Achievement Division (STAD) cooperative learning model, along with video learning media, affects student learning results. With a quantitative approach, the researchers used the Pre-test Post-test Nonequivalent Control Group Design. Test and non-test data gathering methods were used. The experimental class was 32 students from SMPN 1 Sidoarjo from class VII-B, and the control class was 32 students from class VII-C. One science teacher and one science student served as observers in this investigation. Pre-test and post-test sheets, student response surveys, and learning implementation sheets were among the instruments used. Quantitive data used in the data analysis technique. The learning outcomes in this study were based on the post-test paired t-test at ? = 0,05 getting the value of tcount = 8,02 and ttable = 2,040 where tcount > from ttable, indicating that using the cooperative model type Student Team Achievement Division (STAD) assisted by learning video media has an effect on student learning outcomes on the interaction of living things with their environment. Student answers to STAD learning aided by video media are extremely favorable, with an average percentage value of 95.70, placing them in the very good category. According to the high success rate in the implementation of learning in the experimental class at the first meeting, the average percentage was 87,17%, at the second meeting, the average percentage was 97,9% and in the control class, the average percentage was 89,13%, at the second meeting the average percentage was 89,97%. Both classrooms received high marks for learning implementation. Students' enthusiasm and learning outcomes are affected by the usage of the STAD cooperative model and video media. The study concludes that using a STAD type cooperative model in conjunction with video learning media to explore the interactions of living things with their environment can improve student learning outcomes.